Normalization of Global Financial Conditions : The Implications for Brazil - Matheson, Troy (IMF Working Papers; Working Paper ;, 2015)
Global financial conditions are poised to tighten further as the global recovery proceeds. While monetary policy normalization should be a healthy global development as growth continues to recover in advanced economies, financial spillovers seen during the taper episode-which started with the announcement in May 2013 of possible tapering of U.S. asset purchases-hint at potential challenges for Brazil. The Fed's communications related to normalization have improved significantly since the taper episode and, at present, a rise in Fed Funds rate in 2015 is widely anticipated by markets-arguably the most widely anticipated tightening of monetary policy in history. While Brazil could benefit from tighter global financial conditions associated with improved global prospects, bouts of heightened uncertainty about the future course of monetary policy cannot be ruled out. Thus, the correct diagnosis of the underlying reasons behind tighter global financial conditions remains crucially important for Brazil. Adverse spillovers can be mitigated by strengthening policy frameworks and fundamentals.